Implementasi Fingerprint Dan Algoritma Riverst Shamir Adleman Untuk Kemanan Data - Widiyanto, Max Teja Ajie Cipta (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The use of the internet during the pandemic has increased significantly, one of the risks is cyber attacks. Where in the field of online marketing and sales they can sabotage logins. Collect story shop is one of the providers of photography services in the city of Makassar. Currently the process of ordering customer services comes to the office or orders via social media Instagram or WhatsApp so that it has several problems and has not been able to maintain the security and confidentiality of customer data. This study aims to keep the content of the message secret by changing the message to be difficult to understand when sent and unknown to people who have no interest. In this study, fingerprints are implemented for login security. Fingerprint is a technology that uses biometric verification, namely fingerprints, but when the smartphone does not have a fingerprint feature, the data will be secured using the Riverst Shamir Adleman (RSA) algorithm. The RSA algorithm is one of the public key algorithms that has the advantage of a high level of accuracy due to the difficulty of factoring prime numbers. Every data entered into the ordering application is encrypted using the RSA algorithm in the form of numbers stored in the database and will be decrypted again on the application's user interface display. The results show that fingerprints and RSA algorithms can help the process of securing customer data from the results of accuracy testing, so that the contents of secret messages are difficult to understand when sent and are not known by people who are not interested